Penerapan Model Pembelajaran Problem Solving Dalam Meningkatkan Hasil Belajar Matematika Siswa - Erni Sulistiyanti; Sinta Nuriyah; Siti Sarah (Yayasan Darussalam Bengkulu, 2025)
The problem in this study is the low achievement of students' mathematics learning. This problem can be formu- lated as follows